Environmental Ethics from Perspective of the Quran and Sunnah - Yusuf, Muhammad; Marjuni , Kamaluddin Nurdin (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2022)
Environmental ethics is a knowledge of ethics that is based on an ethical approach and used to respond to various environmental crises caused by human behavior. This article refers to verses of the Quran and hadiths as the basis of spiritual and environmental ethics values ​​on human interaction with the environment. It elaborates on verses and prophetic traditions that are relevant for obtaining full inspiration of concepts through interpretations and thematic hadiths. It is achieved by reading the full text withoutseparating the context, after identifying the verses of the Quran and hadiths explored based on the context. The religion established by the Whites’ has been accused as one of the causes of environmental damage. However, despite igniting the reaction of religious refusal, it also encourages the reflection on critical theology and methods of reading sacred texts. In principle, Islam teaches environmental ethics integrated into the concepts of tawhîd, khilâfah, amanah, and akhîrah based on Quran and hadith.